Determinan Loyalitas Pelanggan pada Operator Telepon Selular - Slamet Heri Winarno; Bryan Givan; Y. Yudhistira (Faculty of Economic and Business, 2018)
The Determinants of Customers' Loyalty in Celuler Phone ProviderFor cellular network providers to create customer satisfaction and customer loyalty is very important and become the primary business objectives. The current competition is more on improving the quality of their products and competing with each other to enhance optimal service. This study aims to identify customer loyalty determination through product quality, switching cost, price perceived, and customer satisfaction. The subjects of this study are students of several universities using Indosat IM3 Ooredoo with the number of respondents 170 by using purposive sampling technique. Methods of data analysis using descriptive analysis and inferential analysis using SEM Path Analysis technique. The results showed that 18.1% customer satisfaction variable could be explained by variable switching cost and price perceived. Those variables have a positive impact on customer loyalty. On the other hand, 60.5% customer loyalty variables can explain by price perceived and customer satisfaction variables.DOI: 10.15408/ess.v8i2.7586